NOTICIA DE DOS REPRESENTACIONES DEL «POTNIOS HIPPON» ENCONTRADAS EN LORCA (MURCIA) - Eiroa, Jorge Juan; Martínez Rodríguez, Andrés (Anales de Prehistoria y Arqueología, 1987)
This article contains the first details of the discovery of two reliefs representing the <<Masteor f Animals, in Lorca (Murcia) and describes the archaeological characteristics of the site.